Project-level Women’s Empowerment in Agriculture: Results from cognitive testing in Myanmar - Lambrecht, Isabel B.; Sproule, Kathryn; Synt, Nang Lun Kham; Ei Win, Hnin; Win, Khin Zin (International Food Policy Research Institute, 2020)
When designing and evaluating policies and projects for women’s empowerment, appropriate indicators are needed. This paper reports on the lessons learned from two rounds of pretesting and cognitive testing of the project-level Women’s Empowerment in Agriculture Index (pro-WEAI) in a total of five States/Regions in Myanmar. We assess if respondents understand the modules as intended and which questions require modification based on the cultural context. We find that the questions also present in the abbreviated WEAI are generally well understood, particularly on instrumental and group agency. The challenge to respond to hypothetical and abstract questions did become apparent in the domains representing intrinsic agency, and was problematic for questions on autonomy and self-efficacy. Also, the internationally validated questions on attitudes towards domestic violence were too abstract, and responses depend on the scenario envisioned. We also suggest including an adapted version of the module on speaking up in public, to reinforce the domain on collective agency. Our findings provide an encouraging message to those aspiring to use pro-WEAI, but emphasize the need for continued attention for context-specific adjustments and critical testing of even those instruments that are widely used and deemed validated.